SOCIEDADE CIVIL, REPRESENTAÇÃO E A DUPLA FACE DA ACCOUNTABILITY: cidade do México e São Paulo - Lavalle, Adrian Gurza; Castello, Graziela (Caderno CRH, 2008)
adrianagraziela52Organizações civis desempenham, de modo crescente, funções de representação política. A análise das condições de legitimidade das novas práticas de representação é crucial para a inovação e teoria democráticas. A partir da accountability, assumida como componente sine qua non da representação democrática e como estratégia de pesquisa, este artigo (i) examina empiricamente (com base em resultados de surveys) as noções de representação existentes no seio das organizações civis que assumem funções de representação na Cidade do México e em São Paulo, e (ii) avalia seus mecanismos internos de accountability e suas funções de controle sobre o poder público do ponto de vista da teoria democrática. PALAVRAS-CHAVE: sociedade civil, representação, accountability, legitimidade. CIVIL SOCIETY, REPRESENTATION AND THE DOUBLE FACE OF ACCOUNTABILITY: México city and São Paulo Adrian Gurza Lavalle Graziela Castello Civil organizations carry out, increasingly, functions of political representation. The analysis of the conditions of legitimacy of the new representation practices is crucial for the democratic innovation and theory. Starting from the accountability, assumed as a sine qua non component of the democratic representation and as research strategy, this paper (i) examines empirically (based in surveys results) the existing representation notions among the civil organizations that assume representative functions in Mexico City and in São Paulo, and (ii) it evaluates their internal mechanisms of accountability and their control functions on public government from the point of view of the democratic theory. KEYWORDS: civil society, representation, accountability, legitimacy. LA SOCIÉTÉ CIVILE, LA REPRÉSENTATION ET LES DEUX CÔTÉS DE L’ACCOUNTABILITY: México et São Paulo Adrian Gurza Lavalle Graziela Castello Les organisations civiles développent de plus en plus des fonctions de représentation politique. L’analyse des conditions de légitimité des nouvelles pratiques de représentation est devenue cruciale autantt pour l’innovation que pour la théorie démocratiques. En partant du principe que l’accountability est un élément sine qua non de la représentation démocratique et une stratégie de recherche, : (i) on analyse, dans cet article, de manière empirique (sur les bases des résultats des surveys), les notions de représentation qui existent au sein des organisations civiles assumant des fonctions de représentation à Mexico et à Sao Paulo et (ii) on évalue leurs mécanismes internes d’accountability ainsi que leur contrôle sur les pouvoirs publics, du point de vue de la théorie démocratique. MOTS-CLÉS: société civile, représentation, accountability, légitimité. Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br